PERAN STRATEGIS SEKTOR PERTANIAN DALAM MENINGKATKAN PENDAPATAN SEBAGAI UPAYA PENGENTASAN KEMISKINAN PADA MASYARAKAT PERDESAAN - Kamaruddin, K; Sutanty, Marisa; Oktaviana, Riza (Jurnal Ekonomi & Bisnis, 2024)
This study aims to determine the strategic role of the agricultural sector in increasing income as an effort to alleviate poverty in rural communities. The type of this study was associative. The type of data used was quantitative obtained directly from primary sources, namely respondents totaling 94 rice farmers in Kakiang Village. Data collection uses research instruments in the form of questionnaires. The data collection technique used a research instrument in the form of a questionnaire. Data analysis was carried out using simple linear regression analysis techniques, partial hypothesis testing (t test), and determinant coefficient testing (R2). The results of this study showed that the farming income had a negative and significant effect on poverty levels in rural communities in Sumbawa District. The ability of farming income to effect the poverty level in Sumbawa District was 10.5%, while the remaining of 89.5% was effected by other variables outside this study model, such as economic growth, human development index, and open unemployment rate.